Evaluación del impacto de las redes sociales en las ventas de restaurantes temáticos de comida típica en el Centro Histórico de la ciudad de Quito - Prado Rivadeneira, Diana del Pilar (2015)
Impact of social media on sales of themed traditional restaurants in the historic center of Quito is based on the analysis and implementation of strategies appropriate use of social networks, eliminating paradigms that limit business growth by establishing the current situation restaurants and position in the market through the most visited page Facebook worldwide, through this tool penetrate the minds of consumers of food typical, in order to persuade the purchase, setting aspects of behavior or pattern and satisfy human needs. The analysis process allows progress to improve the knowledge of which was obtained high profits as determining sales strategies in Facebook, identify the impact of sales, product list update, creative advertising campaign, continuous training plan and incentives and customer loyalty. Advertising through Facebook provides an opportunity to segment and understand the profile of customers in direct communication, because of its easy access gives us a saving in time, space and money.